Óptima asignación de recursos energéticos para respuesta de la demanda por vehículos eléctricos usando algoritmos húngaros - Meza Cartagena, Jhonatan Fabricio (2018)
The response to the demand (DR) with respect to the load of the network due to the insertion of electric vehicles (VE) has aroused great interest for the impact of these on the electrical systems that is why this document the demand to the impact that the EVs and the different types of load can generate to an electrical network with different scenarios. We present a heuristic model that is based on the Hungarian algorithm, that is, in this specific work we aim to obtain the appropriate allocation of energy resources for the loading of the EVs. Raising several load scenarios that focus on the DR between which has been modeled and determined the types of load that are used: a) slow, (b) fast and (c) ultra-fast that allowed us to evaluate the different behaviors. It also describes the different types of batteries and the EVs they are using, they also have a DR taking advantage of the penetration of conventional and unconventional energies and also with the influence of solar radiation in the winter and summer cases.